The Role of Combined Radiotherapy and Immunotherapy in Locally Advanced Non-small Cell Lung Cancer - Muto, Matteo; Spagnuolo, Alessia; Gridelli, Cesare (Archives of Clinical and Biomedical Research, 2020)
Immune checkpoint inhibitors (ICIs) have recently transformed the landscape for patients with locally advanced non-small cell lung cancer (NSCLC). The addition of consolidation durvalumab after definitive chemo-radiotherapy improved progression-free and overall survival in unresectable stage III NSCLC patients. Experimental evidence of the potential of radiotherapy to enhance anticancer immunity has increased interest in combining radiotherapy and immunotherapy, particularly in the concurrent treatment modality. Being a complex setting, stage III NSCLC treatment cannot be separated from the involvement of a multidisciplinary team for the adequate identification and management of patients. Trials on the efficacy and safety of therapeutic strategies combined with radiotherapy, immunotherapy and chemotherapy for stage III disease are ongoing. Future studies should answer current questions about radiotherapy (timing, sequencing, dose and fractionation) and biomarkers in order to achieve better patient selection and more favorable survival outcomes.